Solutions and comparison theorems for anticipated backward stochastic differential equations with non-Lipschitz generators - XU, Xuecheng; Chen, Min (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
This paper is devoted to solving multidimensional anticipated backward stochastic differential equations (anticipated BSDEs for short) with a kind of non-Lipschitz generators. We establish the existence and uniqueness result for L2 solutions of this kind of anticipated BSDEs, and establish the corresponding one-dimensional comparison theorems for the type of anticipated BSDEs. Our results improve some known results.